Modelling unsaturated dual-phase flow through crushed ores for heap leaching - S. W. Robertson; J. Petersen (The Southern African Institute of Mining and Metallurgy, 2024)
Heap leaching is used extensively for the processing of low-grade copper, gold, and uranium ores. The hydrodynamics is often the most important factor that limits the rate of metal recovery. Over the past decades the author has performed physical and hydraulic testing of a large number of ore samples considered for heap leaching. The data were reviewed to investigate the effect of physical properties such as particle size distribution (PSD) and bulk density on the hydrology. The unsaturated flow through the bed is traditionally modelled with soil science models such as Brooks-Corey (BC) and Van Genuchten-Mualem (VGM), which relate the hydraulic conductivity to the degree of saturation, also known as the hydraulic conductivity function (HCF). However, most authors found a disconnect between the saturated hydraulic conductivity (KS) and the rest of the HCF, which is explained as resulting from a transition from capillary-to gravity-controlled flow. However, the author found no such transition, and found the flow to be governed by capillary flow throughout. Traditional BC or VGM fits were found to be appropriate, however it was necessary to modify the model to include a point of inflection, above which the hydraulic conductivity remains constant while the moisture content keeps on increasing. It was proposed that this is the result of unconnected or poorly connected pores, which fill with solution but do not create additional flow channels. The point of discontinuity was also found to correspond with the air entry point, measured independently from the air conductivity curves. On average, the air entry point corresponds to the experiential rule that the void saturation should remain below 65% for aerated heaps.